Investigação de atividade citotóxica de complexos de Rutênio (II) e suas interações com BSA - CAMPOS, Vanessa Niely Soares (2018)
The work focuses on the synthesis and characterization of new ruthenium (II) compounds containing foreign amino acids (L-Alanine, L-Methionine, L-Tryptophan and L-Acid Glutamic) and non-chiral (Glycine) and bisphosphines, interests. The new compounds have the general formula [Ru (AA)(dppm)2]PF6, where AA refers to the linking amino acids, dppm corresponds to 1,1-bis(diphenylphosphino) methane. All components performed were characterized by nuclear magnetic resonance spectroscopy, 31P{1H}, 1H, 13C{1H} and their two-dimensional correlations, infrared and Uv-visible region absorption spectroscopy, cyclic and square wave voltammetry, molar conductivity, elemental analysis and X-ray diffraction by single crystal. They were analyzed for cytotoxic activity in the A549 (lung carcinoma), MDA-MB-231 (metastatic breast adenocarcinoma) and normal MRC-5 (human lung fibroblasts) lineage, as well as promising. The interaction mechanism of the prototypes was involved in the study of the interaction with bovine serum albumin (BSA).